Integrasi STEM dalam Pembelajaran Matematika Abad ke-21: Sebuah Systematic Literature Review - Simamora, Ruth Maya; Astawa, I Wayan Puja; Suryawan, I Putu Pasek (Media Pendidikan Matematika, 2026)
The Science, Technology, Engineering, and Mathematics (STEM) approach has emerged as a prevailing paradigm in twenty-first-century mathematics education, consistently demonstrating its capacity to enhance students' higher-order thinking competencies. Despite the rapid proliferation of studies on STEM implementation in mathematics education, systematic reviews that comprehensively map research trends, implementation models, and their implications remain scarce. This study aims to analyze research trend patterns, forms of implementation, and the implications of the STEM approach in mathematics learning through a Systematic Literature Review (SLR) guided by the PRISMA protocol. Data were drawn from 28 Scopus-indexed articles published between 2020 and 2026. The novelty of this study lies in the systematic identification of three dominant patterns:(1) the predominance of PJBL/PBL as the primary implementation model; (2) an emerging shift in recent research (2025–2026) toward the integration of Artificial Intelligence (AI) and digital technology within STEM ecosystems; and (3) a consistent pattern of improvement in students' critical thinking, creativity, problem-solving skills, learning motivation, and engagement across diverse educational contexts and levels. These findings offer a conceptual map that serves as an empirical reference for researchers and practitioners in designing mathematics instruction that is innovative, meaningful, and responsive to the demands of the twenty-first century.